Effects of treatment on the histopathology of leprosy. Issue 4 (April 1995) - Cree, I A; Coghill, G; Subedi, A M; Abbot, N C; Butlin, S R; Samson, P D; Beck, J S
Abstract : AIMS--To identify the histological changes in leprosy skin lesions over the first few weeks after the start of leprosy treatment and to examine their relationship to reversal reaction. METHODS--Sequential skin biopsy during treatment with multiple drug therapy. In this study, a series of 28 patients was studied, from whom two or more biopsies were taken at two week intervals. Fourteen patients had paucibacillary leprosy (PBL) and 14 had multibacillary leprosy (MBL). RESULTS--In most cases, granuloma fraction and bacterial index fell during treatment, the bacterial index being less sensitive than the granuloma fraction. Since the biopsies were fixed in buffered formalin and processed through to paraffin wax, little immunohistochemistry was feasible. However, there was strong evidence of immune activation, with increased expression of HLA-DR in the granulomas of MBL and PBL cases: the epidermis also expressed HLA-DR in several patients. Such changes may reflect gamma IFN production from granuloma lymphocytes. Patients with reversal reaction often showed HLA-DR expression on admission which decreased with corticosteroid treatment. CONCLUSIONS--The results suggest that activation of cell mediated immunity in leprosy lesions occurs during treatment with multiple drug therapy and may not be restricted to those with clinical evidence of reversal reaction.